Prospective, Double-Blind Evaluation of Umbilicoplasty Techniques Using Conventional and Crowdsourcing Methods. Issue 6 (December 2017) - van Veldhuisen, Charlotte L.; Kamali, Parisa; Wu, Winona; Becherer, Babette E.; Sinno, Hani H.; Ashraf, Azra A.; Ibrahim, Ahmed M. S.; Tobias, Adam; Lee, Bernard T.; Lin, Samuel J.
Abstract : Background: Umbilical reconstruction is an important component of deep inferior epigastric perforator (DIEP) flap breast reconstruction. This study evaluated the aesthetics of three different umbilical reconstruction techniques during DIEP flap breast reconstruction. Methods: From January to April of 2013, a total of 29 consecutive patients undergoing DIEP flap breast reconstruction were randomized intraoperatively to receive one of three umbilicoplasty types: a diamond, an oval, or an inverted V incision. Independent plastic surgeons and members of the general public, identified using an online "crowdsourcing" platform, evaluated aesthetic outcomes in a blinded fashion. Reviewers were shown postoperative photographs of the umbilicus of all patients and a four-point Likert scale was used to rate the new umbilicus on the size, scar formation, shape, localization, and overall appearance. Results: Results for the focus group of independent plastic surgeons and 377 members of the public were retrieved ( n = 391). A total of 10 patients (34.5 percent) were randomized into having the diamond incision, 10 (34.5 percent) had the oval incision, and nine (31.0 percent) had the inverted V incision. Patients were well matched in terms of overall characteristics. The general public demonstrated a significant preference for the oval incision in all five parameters. There was no preference identified among surgeons. Conclusion: This study provides evidence that a sample of the U.S. general public prefers the aesthetics of the oval umbilicoplasty incision, which contrasted with the lack of preference identified within this focus group of plastic surgeons. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.